MOTIVASI INDONESIA BEKERJASAMA DENGAN HONGKONG DALAM EKSPOR IKAN KERAPU TAHUN 2012-2014 (StudiKasus: Kota Batam) - Rika Dwi Ransih; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This Research explains about the Motivation Of Indonesia Cooperate With Hongkong in Export of Groupers Fish 2012-2014 which focused In Batam City. Grouper fish has become a trademark (brand) and an icon for the area around the islands of Batam. The Advantages of grouper fish is a very high price and its market share is almost unlimited. Grouper market expanding with increasing interest in the East Asian population to consume these fish. The high demand for exports of grouper fish can increase the income of fishermen and reduce the poverty. Hongkong is the one of world's largest exporter of grouper fish.The method that is used in this research is qualitative research. The datas has taken from field research which is based in Batam, books, journals, article,websites and other sources that are involved with the research. This research uses liberalism perspective and nation state analysis level.From this analysis it is concluded that Indonesian motivation to cooperate with hongkong in the export of groupers fish because Indonesia and Hongkong have a good cooperation in the fishery sector and the demand of groupers in Hongkong has been increased and the quality of grouper in Indonesia is good especially in Batam.Keywords : Indonesia, Hongkong, Groupers fish, cooperation, export, markets